Literal Equation: Help solve
3x-4y = 26
x - 8y = 22

- anonymous

Literal Equation: Help solve
3x-4y = 26
x - 8y = 22

- Stacey Warren - Expert brainly.com

Hey! We 've verified this expert answer for you, click below to unlock the details :)

- jamiebookeater

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

- amistre64

3x-4y = 26 (-2)
x - 8y = 22
-6x+8y = -52
x - 8y = 22
-------------
-5x = -30
x = 6

- anonymous

x=6,y=-2

- anonymous

Why do you only subtract -2?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

he is multiplying the whole equation with -2

- amistre64

you mulltiply the whole thing by (-2) in order to get an equation that can eliminate a variable

- anonymous

And you are elimination the Y?

- amistre64

yes; with the y gone, we can easily solve for x

- anonymous

What about substitution?

- amistre64

for example:
3x = 12; x=4
what happens if we multiply the whole thing by 5, does the x value change?
3x = 12 (5)
15x = 60 ; x = 4

- amistre64

substitution is just solving for one variable in the terms of the other ... its more labor intensive

- amistre64

subbing, elimiation, matrix .... all get the same answer so you eventually just go with whats best for you :)

- anonymous

Except rumor has it that this problem will be on a test with subbing instead!

- amistre64

How do you get to kentucky? lol

- amistre64

then solve for one variable in terms of the other; use that 'value' in the other eqaution to get a solid value for the 'other' variable; and use the solid value to determine the value of the unknowned

- anonymous

What if i took
3x - 4y = 26
x - 8y = 22 and i did this x = 22 + 8y
would that work?

- amistre64

that would work out great :)

- amistre64

since x=x=x=x=x... use that 'value' for x in the top and solve it all for y

- anonymous

Are you saying 3(22 + 8y) - 4y = 26
66 + 24y - 4y = 26

- amistre64

thats correct

- anonymous

Why do I flip it the 2nd equation though?

- amistre64

becasue you cant really determine the value of y from the first equation; you need another 'form' to use it in to calibrate the value

- amistre64

umm.... what do you mean by flip it?

- anonymous

Changing it from x - 8y = 22 to x = 22 + 8y

- amistre64

think of subbing as 'looking at it from another direction'...

- amistre64

x + y = 6 can have any values; and you cant determine x or y to be one point ..... so look at it thru a different equation right?

- anonymous

So in the
x - y = 4
4y - x = 14
could I change the x - y = 4 to x = 4 + y?

- amistre64

yes..... then we use that 'value' in the other equation to see it from a different perspective and can solve for y in it

- anonymous

or in the equation
x + y = 10
6x - 7y = 34
I can change the x + y = 10 to x = 10 - y?

- amistre64

exactly

- anonymous

I think I get it. If I don't I'll just ask you again :D

- amistre64

good idea ;)

Looking for something else?

Not the answer you are looking for? Search for more explanations.